Role of Azolla in sustainable agriculture and climate resilience: a comprehensive review - Yang, Youquan; Yang, Yanqiu; Deng, Sufang; Ying, Zhaoyang (Frontiers in Plant Science, 2025)
Agriculture faces mounting challenges from climate change, soil degradation, and unsustainable agrochemical use, highlighting the need for eco-friendly solutions. Azolla, a fast-growing aquatic fern, has emerged as a multifunctional resource for sustainable farming and climate resilience. Through its symbiosis with Anabaena azollae, it fixes atmospheric nitrogen, reducing dependence on synthetic fertilizers and improving soil health. Azolla also serves as a protein-rich feed for livestock and aquaculture, suppresses weeds and pests in rice systems, and supports water conservation. Beyond agriculture, it contributes to carbon sequestration, mitigates methane emissions, and shows promise in wastewater treatment, bioremediation, and as a feedstock for biofuels and bioplastics. However, large-scale adoption is limited by challenges such as short shelf life, ecological risks, and preservation constraints. This review synthesizes current knowledge on Azolla, emphasizing its biological and ecological functions, highlights practical applications across agriculture, livestock, aquaculture, and environmental management, and outlines key research priorities needed to overcome limitations and enable its integration into climate-smart agricultural and environmental systems.